Respirasi Tanah Akibat Sistem Olah Tanah dan Aplikasi Mulsa In Situ pada Pertanaman Kacang Hijau (Vigna radiata L.) di Laboratorium Lapang Terpadu, Universitas Lampung - Yuves Menti; Sri Yusnaini; Henrie Buchari; Ainin Niswati (Jurnal Agrotek Tropika, 2020)
Soil respiration is an indicator of the activity of microorganisms in the soil. The treatment of soil tillage system and the use of organic mulch given to the soil will affect the activity of soil microorganisms. The research aims to study the effect of soil tillage systems, application of in situ mulch, and the interaction between both in soil respiration. This research was conducted from April to July 2017 at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung, using a Randomized Block Design (RBD) factorially prepared with two treatment factors. The first factor is the soil tillage system (T), which consists of minimum tillage (T0) and conventional tillage (T1). The second factor is the treatment of mulch (M), which consists of no mulch (M0) and the application of in-situ mulch 5 t. ha-1 (M1). The data obtained were tested for various homogeneity by the Bartlett test and additivity by the Tukey test. Data were analyzed by analysis of variance and continued with LSD test at a 5% level. The relationship between soil temperature, soil moisture content, soil organic matter, and soil pH with soil respiration was tested by correlation test. The results showed that the soil tillage system and application of in-situ mulch had no significant effect on soil respiration, and there was no interaction between the soil tillage system and application of in-situ mulch in soil respiration on observations before tillage, 1 day after planting (HST), 41 HST, and 88 HST. There is no correlation between soil temperature, soil moisture content, soil organic matter, and soil pH with soil respiration on pre-tillage observations, 1 HST, 41 HST, and 88 HST.